The Design Productivity Debate 1998
DOI: 10.1007/978-1-4471-1538-0_8
|View full text |Cite
|
Sign up to set email alerts
|

The Design Co-ordination Framework: key elements for effective product development

Abstract: The Strathprints institutional repository (https://strathprints.strath.ac.uk) is a digital archive of University of Strathclyde research outputs. It has been developed to disseminate open access research outputs, expose data about those outputs, and enable the management and persistent access to Strathclyde's intellectual output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Design is a very complex and multi-disciplinary activity, and the information 4 involved is both dynamic and semantically rich (Boston et al 1998;Andreasen et al, 1998). This section presents a brief literature review on the nature of the design activity, pointing out some important features that must be considered in the development of process models.…”
Section: The Nature Of the Design Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Design is a very complex and multi-disciplinary activity, and the information 4 involved is both dynamic and semantically rich (Boston et al 1998;Andreasen et al, 1998). This section presents a brief literature review on the nature of the design activity, pointing out some important features that must be considered in the development of process models.…”
Section: The Nature Of the Design Activitymentioning
confidence: 99%
“…In fact, some authors have pointed out that the results of research on design modelling have had a limited impact in the industry because most studies regarded design as a relatively autonomous and bounded activity, and did not take into account business issues such as availability of resources, time constraints, and organisational structure, which are essential considerations for conducting effective design (Andreasen et al, 1998;Maffin, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been demonstrated that most of the product characteristics and costs depend on decisions taken at the early design stages (Andreasen et aL 1997), DFX-type knowledge should be available and used as from the conceptual design stage when the solution is still evolving. However, current manual and computer based design approaches, do not adequately support designers in handling the phenomena of propagation effects during synthesis, by foreseeing and exploring life-cycle consequences (LCCs) co-evolving with their synthesis decisions (Borg 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Those in favour of distributed control frameworks usually refer to bottlenecks and catastrophic failure as being shortcomings of centralised frameworks, whilst those in favour of centralised control frameworks refer to significant increases in network and processing requirements and overall complexity as being shortcomings of distributed frameworks. Rarely, however, has anyone considered the management of distributed coordination from an engineering design perspective (Andreasen et al 1996;Coates et al 1999Coates et al , 2000aWhitfield et al 2000), and more importantly, from the requirements of the engineering designer.…”
Section: Centralised and Distributed Coordination Controlmentioning
confidence: 99%